Interventionism in the labor market: The real effects of the FGTS - Salzer, Thais (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2022)
The Fund for Employees (FGTS) was created by the Federal Government of Brazil to "protect" the worker fired without just cause. According to the rules, the account balance of FGTS is formed by monthly and mandatory deposits made by the employer. Employees can withdraw their money at particular moments, as defined by the government. This article aims to analyze the real effects of this regulation in Brazil and evaluate the benefits of extinguishing this fund. This government intervention interferes in the environment of voluntary exchanges between employees and employers, increasing the cost of the worker. It also creates the adverse effect of increasing <!– Que tal: “it also increases the turnover?” Se o seu foco era enfatizar o fato de ser um efeito adverso, melhor deixar como está no texto. –>turnover in the labor market because it encourages the worker to act in a way that motivates a dismissal to gain access to this resource. The preference for resources at present is observed when analyzing the results of the resource flexibility measure that took place in 2019. More than 12 million workers chose to anticipate receiving their resources. In addition, the financial return of the FGTS is very low for its shareholders. The data show that the money stuck in the FGTS yields below the average returns of similar risky applications. Who gains from this is the government, which can use the cheap resources of this fund. This way, the end of the FGTS in Brazil would significantly improve productivity and allocations in the Brazilian labor market.